2018
DOI: 10.1055/s-0038-1667317
|View full text |Cite
|
Sign up to set email alerts
|

Number of Preoperative Hyperhidrosis Sites Does Not Affect the Sympathectomy Postoperative Results and Compensatory Hyperhidrosis Occurrence

Abstract: Patients with more than one preoperative hyperhidrosis site present worse quality of life prior to surgery than those with a single hyperhidrosis site, but the number of hyperhidrosis sites before surgery does not affect surgery outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Recurrence hyperhidrosis requiring re-operation and chronic pain was not observed in any patient during the follow-up process (HDSS > 3). The mean PHSS of all patients was 8.1 (range, [3][4][5][6][7][8][9][10][11][12][13][14], and there was a statistically significant difference between the groups in terms of PHSS (►Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrence hyperhidrosis requiring re-operation and chronic pain was not observed in any patient during the follow-up process (HDSS > 3). The mean PHSS of all patients was 8.1 (range, [3][4][5][6][7][8][9][10][11][12][13][14], and there was a statistically significant difference between the groups in terms of PHSS (►Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the reason for observing no changes in the QOL after sympathectomy is related to surgical failure, and this failure rate is around 5%. 12 Surgical failure can be defined as observing no decrease in the main complaint site in the short/medium term. This possibility is an important issue, like the presence of RS, that should be discussed with the patient in the preoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure commonly used for the treatment of palmar hyperhidrosis is one-stage (under the same anesthetic act) bilateral thoracic sympathectomy by videothoracosocopy [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…The wide variability of CS incidence can be affected by several factors like heterogeneous patient populations, a variety of sympathetic denervation techniques, or more important to a lack of objective methodology for defining CS [ 6 , 11 , 12 ]. In order to reduce the incidence of CS, some authors have studied the two-stage operative treatment, which consists of the initial approach of the dominant limb followed by contralateral limb surgery at a later time.…”
Section: Introductionmentioning
confidence: 99%